2016
DOI: 10.3389/fmicb.2016.02095
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of the Bacterial Microbiota of Anopheles Mosquitoes from Binh Phuoc Province, Vietnam

Abstract: The naturally acquired microbiota of Anopheles can influence vector’s susceptibility to Plasmodium and its capacity to transmit them. Microbiota modification is a new challenge to limit disease transmission but it still needs advanced knowledges on bacterial community in Anopheles, especially in wild and infected specimens from diverse origin and species. Bacterial culture and 16S rRNA gene-PCR associated to Temporal Temperature Gradient Electrophoresis (TTGE) were applied to explore the bacterial diversity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
27
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 62 publications
11
27
0
Order By: Relevance
“…This trend was replicated in the other study sites. Thus, it is clear from these results that variation in microbiota between mosquito species may occur in some sampling locations but not in others, which is consistent with previous findings [ 32 34 , 55 ].…”
Section: Discussionsupporting
confidence: 92%
“…This trend was replicated in the other study sites. Thus, it is clear from these results that variation in microbiota between mosquito species may occur in some sampling locations but not in others, which is consistent with previous findings [ 32 34 , 55 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our ndings are consistent with previous studies that showed that collection site was a major contributor to the microbial diversity of eld-caught Anopheles mosquitoes [26,[49][50][51]. For example, Muturi et al…”
Section: Discussionsupporting
confidence: 93%
“…bacteria, which correspond to the most abundant taxa associated with those populations [ 18 ]. In Vietnam, Acinetobacter was found to be the sole core microbiota constituent of 11 Anopheles species [ 30 , 31 ]. Indigenous and invasive populations of Ae.…”
Section: Mosquito Core- and Pan-microbiotamentioning
confidence: 99%